GOVERNMENTALITY: CASES OF THE RAYJA HOTEL CONFLICT CONSTRUCTION PERMIT, BUMIAJI SUB-DISTRICT, BATU - Friska Ayu O; Mardiyono ,; Andy Fefta Wijaya (REFORMASI, 2019)
Governance concept implies a shift in the role of the government, private sector and community, so that it necessary synergy in the implementation of the government. Community involvement in policy formulation needed to build the quality of local government. In reality, this ideal has not been able to be implemented in developing countries, in particular Indonesia. In Batu City, there is resistance against the construction of hotel residents who opposed the Rayja Local Regulation no. 7 of 2011 on Spatial Planning state that Sumber Gemulo is a protected area. Differences in knowledge caused a power space on each of the actors, in particular the Government. Space power it seeks to create a discourse by the main actor, Mayor. A series of regulatory practices that occur as a strategy of "disciplining” and "tourism city" as a discourse. It also has affected to create a new claims and governmentality among actors. This research used explanatory - case study method. To minimize bias in the classification of the actor then analyzes that support this research is Narrative Policy Analysis (NPA). This research was conducted in Batu City, East Java Province. The results of this study prove that the government is in the process of giving the IMB Hotel Rayja is not regulatory governance practices.